INSP-09. Using genetically engineered mouse models and patient-derived orthotopic xenografts to develop new therapies for pediatric brain tumors. (3rd June 2022) - Jonchere, Barbara; Pribnow, Allison; Morfouace, Marie; Shelat, Anang; Yu, Jiyang; Rankovic, Zoran; Gajjar, Amar; Northcott, Paul A; Robinson, Giles W; Roussel, Martine F
Abstract: Medulloblastoma is the most common malignant pediatric brain tumor. Extensive molecular analysis by many groups around the world demonstrated four distinct subgroups, WNT, SHH, Group3 and Group4 that now all have been divided into 11 total subtypes, 8 for Grou3 and Group4 medulloblastoma. SHH with MYCN amplification and TP53 mutations and Group3 with MYC amplification are the most aggressive and the least curable with few to no therapeutic options for recurrent tumors. Over the last two decades, my group developed several murine models for Group3 with MYC and SHH with MYCN overexpression and p53 loss of function and patient-derived orthotopic xenografts that recapitulate the four tumor subgroups. In addition, several human Group3 medulloblastoma lines with MYC amplification have been established in 2D and 3D cultures. I will discuss how the development of these murine and human medulloblastoma models combined with high throughput drug screens and pre-clinical trials at St. Jude led to the identification of new therapies currently evaluated in clinical trials.